Tissue Factor Pathway Inhibitor Inhibits Aortic Smooth Muscle Cell Migration Induced by Tissue Factor/Factor VIIa Complex - Sato, Yuichiro; Asada, Yujiro; Marutsuka, Kousuke; Hatakeyama, Kinta; Kamikubo, Yuichi; Sumiyoshi, Akinobu (Thrombosis and Haemostasis, 1997)
Tissue factor (TF), a transmembrane glycoprotein, forms a high affinity complex with factor Vll/VIIa (FVIIa) and thereby initiates blood coagulation. Tissue factor pathway inhibitor (TFPI) is an endogenous protease inhibitor of TF/FVIIa-initiated coagulation. We previously reported that TF was a strong chemotactic factor for cultured vascular smooth muscle cells (SMCs). In this study, we examined the contribution of FVIIa and the effect of TFPI to TF-induced cultured SMC migration. TF/FVIIa complex showed a strong migration ability, however, neither TF alone nor FVIIa induced SMC migration. TF/FVIIa treated by a serine protease inhibitor and the complex of TF and inactivated FVIIa (DEGR-FVIIa) did not stimulate SMC migration. Pretreatment with hirudin and the antibodies to a-thrombin and factor X had no effect on TF/FVIIa-induced SMC migration, although a-thrombin and factor Xa also induced SMC migration respectively. TFPI markedly inhibited TF/FVIIa-induced SMC migration in a concentration-dependent manner, but did not affect the SMC migration induced by platelet-derived growth factor (PDGF)-BB, basic fibro blast-growth factor (bFGF), or a-thrombin. These results indicate that the catalytic activity of TF/FVIIa complex is important on SMC migration, and TFPI can reduce SMC migration as well as thrombosis.